ASPEK FAKTOR LINGKUNGAN FISIK DAN PERILAKU TERHADAP KEJADIAN MALARIA DIDAERAH ENDEMIS - Santoso, Raden Bagus Edy; ND, Dian Mahanani; Sulistiyani, Sulistiyani; Kelabora, Jonathan (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Malaria is an infectious disease that continues to be a major challenge in public health. The Silau Laut Health Center working area shows that several villages, especially in Silo Baru village, have a high risk of malaria. The purpose of the study was to determine the relationship of aspects of physical environmental factors (Presence of Swamps) and behavior to the incidence of malaria in endemic areas. The research design used in this study was cross sectional. The research was conducted at the Silau Laut Health Center. The research was conducted in September 2023. The study population is all people in the working area of the Silau Laut District Health Center, which is 23,356 people. The sample amounted to 68 respondents. The sampling technique used purposive sampling. The research instrument used a research questionnaire. Data analysis was carried out univariate and bivariate. The results showed a relationship between the presence of swamps (p value: 0.000) and the behavior of using mosquito nets (p value: 0.046) to the incidence of malaria. It is recommended that the community pay more attention to the environmental conditions around the house by carrying out environmental management activities to reduce the potential existence of breeding places and resting places. These activities can include hoarding, draining, cleaning and draining clogged waterways and trimming bushes.Keywords: Swamp Presence, Malaria, Mosquito Net Use